Mapping the World Population One Building at a Time - Tiecke, Tobias G.; Liu, Xianming; Zhang, Amy; Gros, Andreas; Li, Nan; Yetman, Gregory; Kilic, Talip; Murray, Siobhan; Blankespoor, Brian; Prydz, Espen B.; Dang, Hai-Anh H. (World Bank, Washington, DC, 2020)
High resolution datasets of population density which accurately map sparsely distributed human populations do not exist at a global scale. Typically, population data is obtained using censuses and statistical modeling. More recently, methods using remotely-sensed data have emerged, capable of effectively identifying urbanized areas. Obtaining high accuracy in estimation of population distribution in rural areas remains a very challenging task due to the simultaneous requirements of sufficient sensitivity and resolution to detect very sparse populations through remote sensing as well as reliable performance at a global scale. Here, the authors present a computer vision method based on machine learning to create population maps from satellite imagery at a global scale, with a spatial sensitivity corresponding to individual buildings and suitable for global deployment.